Mental accounting: a systematic review - Cruz, Ione (2019)
This study was motivated by the need to characterize scientific research on the "Mental Accounting" construct in the period 1900 to 2015. Mental Accounting is a branch of Accounting science that aims at guiding individuals to make financial decisions as successful enterprises. Discussion of this topic is usually based on the Perspective Theory. The main objective of this study is to describe and to analyze the progress of Accounting research in the Mental Accounting area in the mentioned period, based on an approach of content analysis. The results confirm the need for Accounting research in the Mental Accounting area, although in recent years a gradual progress and greater interest in it is seen. However, despite being considered a promising area, it is still little explored in the literature. We also note that the consumer and his purchasing decisions are priority issues, with focus on the main concept of Mental Accounting in this area, namely the "Loss Aversion" As a suggestion for future works we propose the investigation of other issues related to the Mental Accounting construct, with the aim of expanding the approaches to the issue.